Konsep Wasīlah Dalam Tafsir Ṣūfī Sunnī Dan Tafsir Ṣūfī Shīʿī - Ashabul Yamin, Mochammad (Maqasid: Jurnal Studi Hukum Islam, 2024)
The concept of Wasīlah in the Islamic tradition refers to the means or intermediariesused by a servant to get closer to Allah. This term explicitly appears in the Qur'an, especially insurah al-Ma'idah verse 35, which instructs believers to seek Wasīlah as part of their worshipand devotion to Allah. In Ṣūfī interpretations, both in the Sunni and Shīʿī traditions, the conceptof Wasīlah receives special attention as an integral part of the spiritual journey towards God.However, there are differences in the interpretation and practice of Wasīlah between the twoschools, which are influenced by theological and spiritual differences. In Sunni Ṣūfīinterpretations, Wasīlah is often associated with acts of worship, prayer, and spiritualintervention through Allah's saints and holy figures who are considered to have closeness toAllah.Througha study of these two traditions, it can be seen that although there are similarities in thegoal of achieving closeness to Allah, there are fundamental differences in the practice andmeaning of Wasīlah. In the Sunni tradition, Wasīlah refers more to spiritual practice through aguardian or murshid, while in the Shīʿī tradition, Wasīlah refers to the Ahlul Bait as holy figureswho have spiritual powers given directly by Allah. This second approach shows the complexityof the concept of Wasīlah in Sufism and its central role in strengthening a Muslim's spiritualrelationship with God. Keyword: Wasīlah, Tafsir Ṣūfī, Sunni, Shīʿī